ASSESSMENT OF FACIES PROPERTIES ARISING FROM THE DEHYDRATION OF BIOLOGICAL FLUIDS (Scientific journal of the Fergana State University, 2024)
Biological fluid is a complex medium reflecting the dynamic stability of the body's internal environment. It can possess various physicochemical and biological properties under the influence of different factors. Saliva, as an example of such a fluid, is an indicator of the body's reactivity. Research shows that saliva has significant potential for use in scientific studies and medical diagnostics due to its unique properties. It can provide information about various physiological and pathological conditions of the body, making it a valuable tool for scientists and medical professionals. Saliva is easily accessible for collection and analysis, allowing it to be used in various medical and scientific applications. Thus, the study of the properties of saliva and other biological fluids opens new possibilities for diagnosis and health monitoring.